Ethylene response factors and their role in plant defence - Núñez-Pastrana, R.; Anderson, J. P.; Singh, Karam (CAB International 2009, 2013)
The APETALA2/ethylene response factor family of transcription factors plays crucial roles in the regulation of gene expression during plant development and the response to biotic and abiotic stress. The Ethylene Response Factor (ERF) subfamily is particularly important in the establishment and the tight regulation of plant defences through a balance of positive and negative transcriptional regulation. The expression of the ERFs is induced by pathogens with different lifestyles and they have been implicated in resistance to biotrophs, necrotrophs, and hemibiotrophs. ERFs achieve this by acting as integrators in the crosstalk between signaling pathways mediated by ethylene (ET), jasmonic acid (JA), and salicylic acid (SA) to modulate gene expression according to the stimuli sensed. This review collates recent findings on the regulation of this family of transcription factors (TFs), including transcriptional and post-translational regulation. While DNA binding is typically conferred through the characteristic AP2 domain, the function of other domains including EDLL and EAR in regulating gene expression is discussed. While AP2/ERFs have been implicated in a range of plant stress responses, this review focuses on ERFs in the context of the plant response to pathogens.